Gerenciamento de anotações de biosseqüências utilizando associações entre ontologias e esquemas XML - Teixeira, Marcus Vinícius Carneiro (Universidade Federal de São Carlos, 2008)
Bioinformatics aims at providing computational tools to the development of genome researches. Among those tools are the annotations systems and the Database Management Systems (DBMS) that, associated to ontologies, allow the formalization of both domain conceptual and the data scheme. The data yielded by genome researches are often textual and with no regular structures and also requires scheme evolution. Due to these aspects, semi-structured DBMS might offer great potential to manipulate those data. Thus, this work presents architecture for biosequence annotation based on XML databases. Considering this architecture, a special attention was given to the database design and also to the manual annotation task performed by researchers. Hence, this architecture presents an interface that uses an ontology-driven model for XML schemas modeling and generation, and also a manual annotation interface prototype that uses molecular biology domain ontologies, such as Gene Ontology and Sequence Ontology. These interfaces were proven by Bioinformatics and Database experienced users, who answered questionnaires to evaluate them. The answers presented good assessments to issues like utility and speeding up the database design. The proposed architecture aims at extending and improving the Bio-TIM, an annotation system developed by the Database Group from the Computer Science Department of the Federal University from São Carlos (UFSCar).
Keywords: Banco de dados; Bioinformática; Anotação de genoma; Projeto de banco de dados; Ontologias; XML; Bioinformatics; Genome annotation; Biological databases; XML databases; Database design; Ontologies; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO